2020
DOI: 10.1038/s41467-020-15701-2
|View full text |Cite|
|
Sign up to set email alerts
|

Spread of pathological tau proteins through communicating neurons in human Alzheimer’s disease

Abstract: Tau is a hallmark pathology of Alzheimer’s disease, and animal models have suggested that tau spreads from cell to cell through neuronal connections, facilitated by β-amyloid (Aβ). We test this hypothesis in humans using an epidemic spreading model (ESM) to simulate tau spread, and compare these simulations to observed patterns measured using tau-PET in 312 individuals along Alzheimer’s disease continuum. Up to 70% of the variance in the overall spatial pattern of tau can be explained by our model. Surprisingl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
207
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 327 publications
(266 citation statements)
references
References 74 publications
20
207
0
Order By: Relevance
“…This disconnect raises questions about whether local levels of the two proteins should be directly related, especially during preclinical stages of AD. There is growing evidence that AD pathology is strongly tied to both structural [29] and functional [13] network connectivity properties in the brain [28,32]. This suggests that abnormal levels of tau phosphorylation may additionally be regulated by the presence of pathological Abeta in distant but connected regions.…”
Section: Discussionmentioning
confidence: 99%
“…This disconnect raises questions about whether local levels of the two proteins should be directly related, especially during preclinical stages of AD. There is growing evidence that AD pathology is strongly tied to both structural [29] and functional [13] network connectivity properties in the brain [28,32]. This suggests that abnormal levels of tau phosphorylation may additionally be regulated by the presence of pathological Abeta in distant but connected regions.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that different neuropathological lesions such as Aβ, NFTs, or Lewy bodies can co-exist in the brains of AD patients (Braak and Braak, 1997;Hamilton, 2000), predicting cross protein interactions. Indeed, several studies have shown that the interaction between Aβ and tau can exaggerate AD pathology (Ribé et al, 2005;Bennett et al, 2017;He et al, 2018;Vergara et al, 2019) and that amyloid deposition, preceding the NFT formation, can actively influence tau spreading to neocortical regions (Braak and Braak, 1997;Hardy and Selkoe, 2002;Jacobs et al, 2018;Vogel et al, 2020). Furthermore, oligomeric forms of Aβ were found to be abundant in synapses of AD patients early in the disease before the appearance of phospo-tau at later stages, suggesting that soluble Aβ oligomers in synaptic terminals are associated with dementia onset and may initiate a cascade that drives phosphorylated tau accumulation and its synaptic spread (Bilousova et al, 2016).…”
Section: Protein Cross-seedingmentioning
confidence: 99%
“…The appearance of dystrophic neurites in a plaque, as a consequence of the microglial reaction to the Ab, in some way facilitates or permits the spread of tau aggregation from the limbic system into the cerebral neocortex [39][40][41]. Several lines of evidence support this idea: imaging studies show that tau spread is accelerated by the presence of Ab [41]; injection of human tau from AD brains into APP-knock in mice with tau-negative neuritic plaques forms tau aggregates initially in plaque-associated dystrophic neurites, before tangles appear [42]; and in humans, tau can aggregate initially in dendrites before tangles appear in the neuronal soma [43] (Figure 1). This 'collision' of Ab and tau, mediated by microglia, in the cerebral neocortex has devastating consequences in terms of promoting neurodegeneration and the consequent development of dementia.…”
Section: The Genetics Of Admentioning
confidence: 99%